Theory of Planned Behavior sebagai Upaya Peningkatan Kepatuhan pada Klien Diabetes Melitus - Lestarina, Ni Nyoman wahyu (Media Kesehatan Masyarakat Indonesia, 2018)
Diabetes mellitus (DM) is a disease that often caused complications that require care and long-term treatment. Preliminary study obtained from 10 respondents, 50% of clients difficult to comply with diet , 60% felt tired and bored to the treatment of diabetes, 10% of clients have regular exercise , and 50% of clients said that fear of complications of DM. The purpose of this study is developing model improved compliance based Theory of Planned Behavior in client type 2 Diabetes Mellitus on Community Health Centre Gundih Surabaya. This study used explanative observational with cross sectional approach. The population in this research is type 2 DM client who lives in community health centre Gundih Surabaya. Sampling technique used purposive sampling and 100 patient obtained as a sample. The variables in this study were age, sex, education, knowledge, attitudes, subjective norms, perceptions of control, intention, compliance management of diabetes and blood sugar levels. Data collection was using questionnaire and analyzed using PLS (Partial Least Square). Statistic analysis result shows there is significant relationship between attitude, subjective norm and percieved behavioral control toward intention with t-value 13,935. There is significant relationship between intention with compliance with t-value 7,80.There is significant relationship between compliance and blood sugar level with t-value 4,592. Theory of Planned Behavior (TPB) stated that behavior could effectd by intention, attitude, subjctive norm and percieved behavioral control.